Beyond the cyborg: performance, attunement and autonomous computation. Issue 2 (3rd July 2017) - Donnarumma, Marco
ABSTRACT: Body technologies, such as prostheses and biosensors, are active means of lived experimentation: they enable forms of hybrid embodiment such as the cyborg, whose diverse representations by artists and performers have infiltrated our societal normative regime. To talk about body politics is therefore to talk about the technologies the body incorporates, how they probe its alleged integrity. Performance theories and practices offer a fertile ground of experimentation with this issue. Yet, there is a tendency to frame body technologies as either material extensions of one's body or external objects one perceives with. Such approaches support technocratic systems of beliefs by eliding immaterial and pre-conscious aspects of technological incorporation, I argue. Key to this argument is the notion of automaticity; a subjective form of psychic attunement with particular technical instruments. The performativity of certain bodily thresholds enables forms of human–machine codependence, where body and technology affect each other through discipline, training and relational economies of desire. As a case study, I offer an autoethnographic analysis of my own performance with an artificially intelligent body technology. This reveals an inherently hybrid and relational corporeality, which confounds the boundaries between human and technical, material and immaterial, perceptual and psychological, conscious and pre-conscious.